Analisis In Silico : Aktivitas Senyawa Antibakteri dalam Zingiber aromaticum terhadap Salmonella typhi - Ade Wina Utari Suherman; Diana Hernawati; Rinaldi Rizal Putra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Typhoid fever is an acute infectious disease of the small intestine caused by the bacterium Salmonella typhi. The prevalence of typhoid fever in the world is 27 million cases per year and causes 200,000 deaths. In Indonesia, it is estimated that the incidence of typhus is 148.7 per 100,000 people per year. Treatment of typhoid fever using ciprofloxacin antibiotics still causes bacterial resistance so that the discovery of herbal ingredients as an alternative to typhoid fever drugs is still being developed. This study aims to look at the potential of the active compound Zingiber aromaticum in terms of physicochemical prediction, pharmacokinetics, binding affinity, and level of toxicity. Previous studies have proven that Zingiber aromaticum has the potential to inhibit Pseudomonas aeruginosa and Salmonella typhi bacteria. The method used is molecular docking between the active compounds Zingiber aromaticum to be compared with the control drug ciprofloxacin as a comparison. As a result, all active compounds of Zingiber aromaticum have potential as drug candidates because they fulfill the lipinski’s rule of five. Zerumbon has the best pharmacokinetic profile compared to ciprofloxacin. Compounds in class 4, 5 and 6 are relatively safer, not mutagenic and not toxic to the liver compared to ciprofloxacin. The compounds that have a better binding affinity value than ciprofloxacin are isokaempferide, (-)-beta-Sitosterol, afzelin, kaempferol 3-(3'-acetylrhamnoside), and 3-O-beta-D-Glucopyranosyl sequentially namely -8,1 kcal/mol, -9.0 kcal/mol, -9.4 kcal/mol, -9.3 kcal/mol and -9.3 kcal/mol. The most valid compounds compared to ciprofloxacin are (-)-beta-sitosterol with RMSD l.b 1.513 and RMSD u.b 2.169.